Clinical Pharmacokinetics in a Patient Care Setting - Kostenbaudeh, Harry B.; Swintosky, Joseph V. (The Nigerian Journal of Pharmacy, 1977)
One of the more dramatic demonstrations of the role of pharmaceutical science in pharmacy practice has been the successful implementation of clinical pharmaco- kinetics service by pharmacists in a patient care setting. Pharmaceutical scientists in pharmaceutical industry and academia have been at the forefront of the modern development of pharmacokinetics and biopharmaoeutics. Since the 1950's they have measured the biologic half-lives of drugs. studied their absorption-distributiom metabolism-excretion characteristics. and have designed various drug dosage forms including sustained release forms, based upon a knowledge of pharmacokinetic principles. (Preview the download for more on the abstract)